2014
DOI: 10.1128/aac.00107-14
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Hydrogen-Bonding Network of P2 bis -Tetrahydrofuran-Containing HIV-1 Protease Inhibitors (PIs) with a Protease Active-Site Amino Acid Backbone Aids in Their Activity against PI-Resistant HIV

Abstract: In the present study, GRL008, a novel nonpeptidic human immunodeficiency virus type 1 (HIV-1) protease inhibitor (PI), and darunavir (DRV), both of which contain a P2-bis-tetrahydrofuranyl urethane (bis-THF) moiety, were found to exert potent antiviral activity (50% effective concentrations [EC 50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…80 Inhibitor 12 displayed excellent retention of affinity against the mutant proteases with 0.8- and 2.6-fold changes. A crystal structure was solved for 12 -bound PR A02 mutant protease to help elucidate the results of the cellular binding assay (Figure 9).…”
Section: (5) Recent Progress Towards Hiv-1 Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Inhibitor 12 displayed excellent retention of affinity against the mutant proteases with 0.8- and 2.6-fold changes. A crystal structure was solved for 12 -bound PR A02 mutant protease to help elucidate the results of the cellular binding assay (Figure 9).…”
Section: (5) Recent Progress Towards Hiv-1 Protease Inhibitorsmentioning
confidence: 99%
“…This interaction was absent with darunavir, which may explain the observed difference in potency. 80 …”
Section: (5) Recent Progress Towards Hiv-1 Protease Inhibitorsmentioning
confidence: 99%
“…The structure also forms weaker hydrogen bonds to the backbone of conserved residues Asp29, Asp30/30’. A later study revealed that GRL-008 maintained wild-type polar interactions in the active site of a highly mutated protease from a clinical isolate [66]. It is noteworthy that DRV also conserves polar bonding with the same mutant and outperformed GRL-008 in antiviral activity against wild type and resistant strains.…”
Section: Investigational Antiviral Inhibitorsmentioning
confidence: 99%
“…Structure solutions were obtained using the molecular replacement (MR) method as described previously (36,37). Briefly, MR was performed using MOLREP (38) through the CCP4 (39,40) interface with WT PR taken from PDB ID 4HLA as a search model.…”
Section: Cells and Virusesmentioning
confidence: 99%